Properties of a Viroid-replicating Complex Solubilized from Nuclei - Rivera-Bustamante, R. F.; Semancik*, J. S. (Journal of General Virology, 1989)
SUMMARY An organelle-free fraction with the ability to synthesize citrus exocortis viroid (CEV) RNA was prepared from nuclei-rich samples taken from CEV-infected Gynura aurantiaca D.C. leaf tissue. This extraction was accomplished in the presence of the detergent sarkosyl. Characterization of the viroid synthetic reaction demonstrated that the solubilized complex retained the properties displayed by intact nuclei. These include optima of 1 mm-MnCl2, 10 mm-MgCl2 and 25 mm-(NH4)2SO4, as well as inhibition by α-amanitin (90% at 4 μg/ml) and by the chelators o-phenanthroline (78% at 5 mm) and hydroxyquinoline (45% at 5 mm). Nucleic acid-binding agents such as ethidium bromide and actinomycin D showed a low, non-specific inhibition at relatively high concentrations. Sucrose gradient sedimentation analysis of the sarkosyl supernatant (SSN) components before and after the RNA synthesis showed that the bulk of the progeny remained associated with the viroid complex which sedimented faster than phenol-treated viroid RNA. A high percentage of the CEV RNA molecules migrated in electrophoresis as the circular form. This suggests that all elements necessary for the synthesis of viroid RNA and processing to circular structures are present in the SSN. This endorses the potential of these subnuclear preparations for the study of the processes involved in viroid replication.
Keywords: viroid replication